2014
DOI: 10.1111/tan.12283
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide HLA‐E nucleotide and haplotype variability reveals a conserved gene for coding and 3′ untranslated regions

Abstract: The human leukocyte antigen-E (HLA-E) locus is a human major histocompatibility complex (MHC) gene associated with immune-modulation and suppression of the immune response by the interaction with specific natural killer (NK) and T cell receptors (TCRs). It is considered one of the most conserved genes of the human MHC; however, this low nucleotide variability seems to be a consequence of the scarce number of studies focusing on this subject. In this manuscript we assessed the nucleotide variability at the HLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 56 publications
11
47
0
1
Order By: Relevance
“…The latter study, which evaluated the variability of the HLA-E 3 0 UTR for the first time, revealed a low rate of nucleotide variation in this segment. Regarding the coding region, E ⁄ 01:01 and E ⁄ 01:03 were found to account for 94% of all HLA-E alleles [18]. Similar results were found in Brazilian Afro-descendants [17], four Chinese Han populations [15], Amerindians from Mexico, Colombia and Chile [14] and different European populations [22].…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…The latter study, which evaluated the variability of the HLA-E 3 0 UTR for the first time, revealed a low rate of nucleotide variation in this segment. Regarding the coding region, E ⁄ 01:01 and E ⁄ 01:03 were found to account for 94% of all HLA-E alleles [18]. Similar results were found in Brazilian Afro-descendants [17], four Chinese Han populations [15], Amerindians from Mexico, Colombia and Chile [14] and different European populations [22].…”
Section: Introductionsupporting
confidence: 66%
“…To date, only 17 alleles and six full-length protein variants have been recognized by the IMGT/HLA (http://www.ebi.ac.uk/ipd/imgt/hla/stats.html, database version 3.20.0). Two major allele groups -HLA-E ⁄ 01:01 and E ⁄ 01:03 -account for most of the HLA-E molecules found in the different populations investigated so far [14][15][16][17][18]. The molecules encoded by these groups differ by a single amino acid substitution, encoded at codon 107 (exon 3), in which E ⁄ 01:01 presents an Arginine and E ⁄ 01:03 presents a Glycine.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, the coding and non-coding allelic regions-respectively, exons and introns (plus 5' and 3' untranslated regions)-and the nature of the peptide presented affect the stability of the messenger (m) RNA and the mature protein. This leads to variable levels of protein expression [19,43,45,[62][63][64]. On the other hand, HLA-F is expressed on the cell surface of lymphocytes only upon activation [52] and can be released into the circulation in a soluble form [32]; however, there is not yet any evidence of the effect of specific genotypes of HLA-F or the level of cell-surface expression.…”
Section: Hla-ib: Role In Histocompatibilitymentioning
confidence: 92%
“…HLA-E molecules act on both the innate and adaptive immune system playing a key role in their modulation [31,32] . HLA-E is represented by only 7 non-synonymous alleles (IMGT/ HLA Database, release 3.22.0, 2015-10-10) and, even so, only two of them (E*01: 01 and E*01: 03) have been show to express relevant molecules for the immune function [33] . These HLA-E molecules are broadly expressed on all cells [34] , presenting in the healthy cells surface a limited set of highly conserved peptides derived from classical HLA class I [35] .…”
Section: Introductionmentioning
confidence: 99%